Symptom Profiles, But Not Prefrontal Neurochemistry, Differentiate ADHD Youth With and Without a Family History of Bipolar I Disorder. Issue 13 (November 2022) - Chen, Constance; Tallman, Maxwell J.; Cecil, Kim M.; Patino, Luis Rodrigo; Blom, Thomas J.; DelBello, Melissa P.; McNamara, Robert K.
Objective: To identify clinical and central features that differentiate ADHD youth with and without familial risk for bipolar I disorder (BD).Methods: Psychostimulant-free ADHD youth (10–18 years) with and without a first-degree relative with BD and healthy controls were enrolled. Bilateral ventrolateral prefrontal cortex (VLPFC) proton magnetic resonance spectroscopy ( 1 H MRS) scans and a range of symptom ratings were performed.Results: A total of n  = 145 youth were enrolled. ADHD youth with a family history of BD exhibited greater manic and depressive symptom severity, ADHD hyperactivity/impulsive symptom severity, and higher parent-reported ratings of dysregulation compared with ADHD youth without a BD family history. Although VLPFC metabolite levels did not differ across groups, choline levels in the left VLPFC correlated with different symptom ratings.Conclusion: Symptom profiles including more severe mood and externalizing symptoms, but not VLPFC neurochemistry, differentiate psychostimulant-free ADHD youth with and without a family history of BD.